Digital Leadership Workshop: Building a Visionary Generation For Educators and Students at Manarul Huda Islamic Boarding School Kilangan, Batang Hari Regency - Sukatin, Sukatin; Hariyanto, Mashudi; Astuti, Andri; Maryam, Maryam (Jurnal Masyarakat Mengabdi, 2025)
This Digital Era Leadership Workshop aims to equip participants with relevant understanding and leadership skills amidst technological developments. This activity was held at the Islamic boarding school and was attended by students and teaching staff. The material presented includes digital leadership concepts, adaptation strategies to technological changes, and the use of digital media for effective leadership. Through interactive sessions and discussions, participants are expected to understand the role of leaders in the digital era and develop skills in managing teams and making technology-based decisions. It is hoped that this workshop will increase participants' awareness and readiness in facing leadership challenges in the modern era.